Effects of Sphagnum Leachate on Competitive Sphagnum Microbiome Depend on Species and Time - Hamard, Samuel; Robroek, Bjorn J. M.; Allard, Pierre-Marie; Signarbieux, Constant; Zhou, Shuaizhen; Saesong, Tongchai; de Baaker, Flore; Buttler, Alexandre; Chiapusio, Geneviève; Wolfender, Jean-Luc; Bragazza, Luca; Jassey, Vincent E. J. (Frontiers in Microbiology, 2019)
Plant specialised metabolites play an important role in soil carbon (C) and nutrient fluxes. Through anti-microbial effects, they can modulate microbial assemblages and associated microbial-driven processes, such as nutrient cycling, so to positively or negatively cascade on plant fitness. As such, plant specialised metabolites can be used as a tool to supplant competitors. These compounds are little studied in bryophytes. This is especially notable in peatlands where Sphagnum mosses can dominate the vegetation and show strong interspecific competition. Sphagnum mosses form carpets where diverse microbial communities live and play a crucial role in Sphagnum fitness by regulating C and nutrient cycling. Here, by means of a microcosm experiment, we assessed to what extent moss metabolites of two Sphagnum species (S. fallax and S. divinum) modulate the competitive Sphagnum microbiome, with particular focus on microbial respiration. Using a reciprocal leachate experiment, we found that interactions between Sphagnum leachates and microbiome are species-specific. We show that both Sphagnum leachates differed in compound richness and compound relative abundance, especially sphagnum acid derivates, and that they include microbial-related metabolites. The addition of S. divinum leachate on the S. fallax microbiome immediately reduced microbial respiration (-95%). Prolonged exposition of S. fallax microbiome to S. divinum leachate destabilised the food web structure due to a modulation of microbial abundance. In particular, leachate addition decreased the biomass of testate amoeba and rotifer predators but increased that of other ciliates with similar feeding habits. These changes did not influence microbial CO2 respiration, suggesting that the structural plasticity of the food web leads to its functional resistance through the replacement of species that are functionally redundant. In contrast, S. fallax leachate neither affected S. divinum microbial respiration, nor microbial biomass. We, however, found that S. fallax leachate addition stabilised the food web structure associated to S. divinum by changing trophic interactions among species. The differences in allelopathic effects between both Sphagnum leachates might impact their competitiveness and affect species distribution at local scale. Our study further paves the way to better understand the role of moss and microbial specialised metabolites in peatland C dynamics.